2008
DOI: 10.1177/0269881108099418
|View full text |Cite
|
Sign up to set email alerts
|

Ziprasidone in the treatment of acute mania: a 12-week, placebo-controlled, haloperidol-referenced study

Abstract: This 12-week, double-blind, two-part study in 438 adults with bipolar-associated acute mania began with a 3-week period comparing ziprasidone (80-160 mg/day) and placebo with haloperidol (8-30 mg/day) as active reference. Changes from baseline Mania Rating Scale (MRS) scores for ziprasidone and haloperidol were superior to placebo from day 2 (P = 0.001) to week 3 (P < 0.001); change from baseline at week 3 was greater for haloperidol than ziprasidone (P or=50% decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 27 publications
0
40
0
2
Order By: Relevance
“…Ziprasidone monotherapy was tested for antimanic efficacy in three double-blind placebocontrolled studies (Keck et al 2003c;Potkin et al 2005b;Vieta et al 2009b), one of them also had haloperidol as an internal comparator . All these studies confirmed the antimanic efficacy of ziprasidone.…”
Section: Ziprasidonementioning
confidence: 99%
“…Ziprasidone monotherapy was tested for antimanic efficacy in three double-blind placebocontrolled studies (Keck et al 2003c;Potkin et al 2005b;Vieta et al 2009b), one of them also had haloperidol as an internal comparator . All these studies confirmed the antimanic efficacy of ziprasidone.…”
Section: Ziprasidonementioning
confidence: 99%
“…Several studies support the efficacy of haloperidol. The first one took place in 1975 [451], while more recent studies support the efficacy of up to 30 mg/day of haloperidol against acute mania, with a response rate of 47-56.1 % vs. a placebo 20-35 % at 3 weeks [341,463,537,565].…”
Section: Methodsmentioning
confidence: 99%
“…During the nine-week extension phase, responses were maintained for the majority of patients receiving active treatments. Ziprasidone showed a superior tolerability profile and lower discontinuation rates during the extension phase (53).…”
Section: Pharmacological Treatment Of Manic Episodesmentioning
confidence: 98%